Bystanders and ethical review of research: Proceed with caution. (22nd October 2020) - Wikler, Daniel
Abstract: Scientists seeking to conduct research with human subjects must first submit their proposals to research ethics committees (Institutional Review Boards [IRBs], in the United States). Some of these studies pose risks to "bystanders, " i.e., people who may be affected by the research but who are not enrolled as study subjects. Should IRBs expand their scope to include oversight over possible harms to bystanders as well as research subjects? This paper presents arguments against this step. Prior review of research with human subjects, despite its evident burden on the research enterprise, is a necessary caution, because the tension between the objectives of humane treatment of research subjects and sound scientific design and procedure has in the past led to serious abuses. This rationale is inapplicable in the case of bystanders. Moreover, in view of the many and varied effects of both research practices and scientific advances on the broader public over time, those who may be considered to be "bystanders" may potentially expand without limit; requiring IRBs to anticipate these distant and long‐term effects as part of prior ethical review could greatly increase its burden and its deterrent effect on research. While conducting research without concern for serious potential harm to bystanders may be irresponsible and unethical, expanding the scope of prior review by IRBs to include risks to bystanders is not required by the principles governing human subjects research, and the costs and burdens of this expansion may outweigh any expected gains.